Water scarcity and food security: alternative futures for the 21st Century - Rosegrant, Mark W.; Cai, Ximing (IWA Publishing, 2001)
Water availability for agriculture - the major water user worldwide - is one of the most critical factors for food security in many regions of the world. The role of water withdrawals in irrigated agriculture and food security has been receiving substantial attention in recent years. This paper addresses key questions regarding water availability and food security, including: How will water availability and water demand evolve over the next three decades, taking into account availability and variability in water resources, the water supply infrastructure, and irrigation and nonagricultural water demands? What are the relationships among water scarcity, food production, and food security? How much of future food production will come from rainfed and irrigated areas? A global modeling framework, IMPACT-Water, is applied to explore answers to these questions using analysis.